IMPLEMENTASI METODE PROBLEM BASED LEARNING DENGAN MEDIA QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Kusmayasari, Ayu Linda; Wijayanti, Rina (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This research is a classroom action research. The results of statistics learning (mean, median and mode) in class VIII A students of SMP PGRI 05 Tirtoyudo show that many still have scores below the Minimum Completion Criteria (KKM), especially in completing practice questions, so this research aims to improve the learning outcomes of class VIII A students by using quizizz media. The subjects in this study were class VIII A students at SMP PGRI 05 Tirtoyudo. This research is a Classroom Action Research (CAR) which was carried out in two cycles. Cycle 1 and cycle 2 went through 4 stages, namely (1) action planning, (2) action implementation, (3) observation, and (4) reflection. The results of the study showed that the mathematics learning outcomes of class VIII A students of SMP PGRI 05 Tirtoyudo increased after using problem-based learning (PBL) methods assisted by quizizz media. This is indicated by an increase in the achievement of the Minimum Completion Criteria (KKM). Based on the observation results, an increase in the percentage of learning outcomes from cycle I to cycle II was obtained from 50% to 85% so that mathematics learning at SMP PGRI 05 Tirtoyudo was said to be successful.